Pro PHP application performance tuning PHP web projects for maximum performance - Padilla, Armando; Hawkins, Tim (Apress, 2010)
Pro PHP Application Performance will help you understand all the technologies and components which play a role in how well your applications run. When seconds can mean the difference between retaining a user and losing a user, it's important for all of us to have optimization as part of our project roadmap. But what components within your application should you analyze? How should you optimize? And how can you measure how well your application is performing? These are some of the questions that are answered in this book. Along the way you will also learn the "why" of optimizing. You'll discover why you should optimize a specific component, why selecting one function over another is beneficial, and how to find and use the optimization tools available to the open source community. You'll also learn how to deploy caching software as well as web server software. Pro PHP Application Performance will also teach you more advanced techniques, such as: Using Xdebug to profile functions that are not running as efficiently as possible. Comparing opcode executed by different PHP functions to narrow the search for functions that run efficiently. Using strace to analyze Apache while your application is served to the user. Once you complete this book you will have a complete sense of where to start optimizing and, most importantly, have the tools which allow you to continue optimizing in other PHP applications going forward.